Programming logic controllers (PLC) using ladder and structured control language (SCL) in MATLAB (2015)
There are different programming languages for Programmable Logic Controllers (PLC), the most common of these is the graphical programming language called LADDER. However, LADDER is not friendly in programs requiring calculations of mathematical equations, for example, to calculate the volume of a tank on level control situations. Alternative languages such as Structured Control Language (SCL) are less studied because of their complexity and unpopular in small and medium industry. In this article, the results LADDER programming language and language are compared with SCL generated by Simulink PLC Coder MATLAB tool taking as a case study the calculating the volume of a tank. Finally, this work shows that the Simulink PLC Coder tool presents an alternative to more efficient development.